2016
DOI: 10.1055/s-0042-100912
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments and Controversies in the Treatment of Resistant Hypertension

Abstract: Resistant hypertension is defined as elevated blood pressure despite the appropriate use of 3 or more antihypertensive drugs, including a diuretic, and constitutes a frequent and important clinical problem with significant disease morbidity and mortality. Several sources of evidence point to the sympathetic nervous system as a major protagonist in this disease entity. The catheter-based, radiofrequency ablation of renal sympathetic nerves (renal denervation) to treat resistant hypertension has sparked great en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The focus then moves to treatment of hypertension in diabetes and reveals a discussion of renin angiotensin aldosterone blockade in general [11] and the role of dual RAS blockade in detail [12]. Besides medical treatment as recently underlined by the PATHWAY-2study [13], there might be alternative options such as yoga [14] or more invasive procedures such as renal denervation [15], which are also discussed extensively in this issue. However one should not underestimate the coincidence of other diseases leading to hypertension, such as primary aldosteronism [16] and renal artery stenosis [17], also reviewed in detail.…”
mentioning
confidence: 99%
“…The focus then moves to treatment of hypertension in diabetes and reveals a discussion of renin angiotensin aldosterone blockade in general [11] and the role of dual RAS blockade in detail [12]. Besides medical treatment as recently underlined by the PATHWAY-2study [13], there might be alternative options such as yoga [14] or more invasive procedures such as renal denervation [15], which are also discussed extensively in this issue. However one should not underestimate the coincidence of other diseases leading to hypertension, such as primary aldosteronism [16] and renal artery stenosis [17], also reviewed in detail.…”
mentioning
confidence: 99%
“…[9] Although there are also invasive methods of treating resistant hypertension, that is, electrical stimulation of the carotid baroreceptors and baroreflex activation therapy, their efficacy in clinical trials needs to be confirmed with phase-3 studies. [10][11][12] The catheter-based radiofrequency ablation of renal sympathetic nerves, that is, renal denervation, has emerged as an effective therapeutic option in addition to the nonpharmacological treatment and antihypertensive drugs. [13] When various add-on drugs for resistant hypertension were compared among themselves in clinical trials and meta-analyses, spironolactone showed the best efficacy, but yet the published data are limited, [14] and additional studies are needed to confirm already published studies.…”
Section: Introductionmentioning
confidence: 99%
“…The focus then moves to treatment of hypertension in diabetes and reveals a discussion of renin angiotensin aldosterone blockade in general [8] and the role of dual RAS blockade in detail [9]. Besides medical treatment as recently underlined by the PATHWAY-2-study [15], there might be alternative options such as yoga [16] or more invasive procedures such as renal denervation [17], which are also discussed extensively in this issue. However one should not underestimate the coincidence of other diseases leading to hypertension, such as primary aldosteronism [10] and renal artery stenosis [11], also reviewed in detail in the current issue of the journal, which you are holding in your hands.…”
mentioning
confidence: 99%